2022
DOI: 10.1177/10780874221090874
|View full text |Cite
|
Sign up to set email alerts
|

‘Whiny, Fake, and I Don't Like Her Hair’: Gendered Assessments of Mayoral Candidates

Abstract: Municipal mayoral elections present a compelling puzzle: what happens when gendered stereotypes about level of government conflict with those about type of office? Although local politics is viewed as communal and more feminine, the mayoral office is a prominent, prestigious position of political leadership that voters may perceive as more masculine. We intervene by analyzing open-ended comments about 32 mayoral candidates from a survey of 14,438 municipal electors in eight Canadian cities. We argue gendered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…In a similar vein, a different study showed that informing voters ahead of time about a significant spending program, as well as the promises and allotments made by mayoral candidates, raised awareness of spending and improved voter understanding of the policies put forth by the candidates. However, this information had no effect on turnout or vote shares (Tolley et al, 2022) [22] . Furthermore, the significance of honesty and making wellinformed choices during the voting process.…”
Section: General Average 296 Averagementioning
confidence: 99%
“…In a similar vein, a different study showed that informing voters ahead of time about a significant spending program, as well as the promises and allotments made by mayoral candidates, raised awareness of spending and improved voter understanding of the policies put forth by the candidates. However, this information had no effect on turnout or vote shares (Tolley et al, 2022) [22] . Furthermore, the significance of honesty and making wellinformed choices during the voting process.…”
Section: General Average 296 Averagementioning
confidence: 99%
“…Two additional articles probe questions related to the relationship between gender and urban democracy. Tolley, Lawlor, and Fortier-Chouinard (2023) consider how voters assess women and men running for mayor in Canadian cities. Contrary to the idea that local office would be more hospitable to women, as they would be perceived as “well-suited” to local issues, voters assessed women mayoral candidates more negatively than male candidates.…”
Section: Can Representation Be Improved? How Would It Matter?mentioning
confidence: 99%
“…They see their findings as offering support for gender quotas. They also assess the presence of women mayors, which we might consider in dialogue with the Tolley, Lawlor, and Fortier-Chouinard (2023) findings; women mayors in Spanish cities had a negative association with government efficiency. Ríos, Guillamón, and Cuadrado-Ballesteros (2023) suggest that social role theory linking female characteristics to responsible behavior in government could explain their findings about councilors; on the other hand, they suggest that women mayors’ decision-making could reflect a different set of individual influences and institutional constraints.…”
Section: Can Representation Be Improved? How Would It Matter?mentioning
confidence: 99%